If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15h = 24 + 11h Solving 15h = 24 + 11h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-11h' to each side of the equation. 15h + -11h = 24 + 11h + -11h Combine like terms: 15h + -11h = 4h 4h = 24 + 11h + -11h Combine like terms: 11h + -11h = 0 4h = 24 + 0 4h = 24 Divide each side by '4'. h = 6 Simplifying h = 6
| 5X^2+4x-288=0 | | 28s+49s^2t= | | 10y+23=4y+13 | | 19x-12=24 | | 12-6x=84 | | 2x+3x-1=68 | | 2w^4-13w^2+15=0 | | 4*x^4-9*x^2+2x+3=0 | | -20=17x-38 | | 10(r-3)=40 | | (x^2-100)(x^2-10)=0 | | 2x+3-x=43+6x | | 6x-1=2(3x+2) | | 6x-1=3(3x+2) | | 100x^2-4y^2= | | 2x(x^2-36)(x^2+16)=0 | | 8x-4=4x+6 | | 7v/3=-35 | | x^2+2x-3=-4x-12 | | 3w+4x-14y+4w+7x+8y= | | -6w=-12/7 | | 2a+4b+6a-3b= | | 2y=14/5 | | 6=2/7w | | 1/3*5/12 | | f(x)=3x^2+8x+5 | | 5/3=9y | | 20-3f=2 | | 3(3M-4)=42 | | 8(x+1)=3(x+2) | | a+ax+b=x+1 | | (w+4)(w+6)=0 |